Wacana Sakti Ki Gusti Ngurah Panji Sakti Dalam Babad Buleleng Analisis Struktur Dan Semiotik - Swandayani, I Gusti Ayu Ima (Humanis; Volume 16. No. 1. Juli 2016)
This study discusses about Wacana Sakti Ki Gusti Ngurah Panji Sakti in a Structural and Semiotics Analysis of Babad Buleleng. The study uses structural and semiotics theory. Structural theory in related to the structure of history literature. This theory was introduced by Jonathan Culler and collaberated by a theory introduced by Darusuprapta. Both theory are used in this study about literature aspects, such as: theme, plot, character, mitology with combination of legend, hagiography, symbolism, and suggestion. Meanwhile, semiotics theory is introduced by Carles Sanders Pierce (1931-1958). The method of this study used three steps. First is collecting data through observation technique and supported by note taking technique. Second, the data were analyzed by using a descriptive method and hermeneutics by note taking technique. Third, the result of data analysis presented by using formal and informal method that were supported by deductive and inductive technique. The structure of Babad Buleleng covers plot, theme, and character. Those structures become one unit of framework in construct a theme which concists of mayor theme; that is authentication, and minor theme which concists of declaration, glorification, sacred. Those themes can build characters so that construct the plot such as broken plot which means cause and result which is constructed with mitology elements, legend, hagiography, symbolism, and suggestion. Meanwhile, the purpose of this literature covers the special quality of character name, weapon, and born mark of Ki Gusti Ngurah Panji Sakti.
Keywords: structure, supernatural power, purpose, and babad